2013
DOI: 10.1111/jocn.12228
|View full text |Cite
|
Sign up to set email alerts
|

Pain, fatigue, disturbed sleep and distress comprised a symptom cluster that related to quality of life and functional status of lung cancer surgery patients

Abstract: Symptoms in lung cancer surgery patients often occurred as cluster during the trajectory of disease. To improve the well-being of patients, attentions need to be focused on developing symptom cluster management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 38 publications
7
65
2
2
Order By: Relevance
“…Congruent with our results, other researchers found a significant negative relationship between symptom burden and functional status of advanced cancer patients [27][28][29][30][31] . In a recent study from Egypt that included patients with metastatic cancer, the total average ESAS score differed significantly according to the Eastern Cooperative Oncology Group (ECOG) performance scale from 34 in patients with an ECOG score of 1 to 70 in patients with an ECOG score…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Congruent with our results, other researchers found a significant negative relationship between symptom burden and functional status of advanced cancer patients [27][28][29][30][31] . In a recent study from Egypt that included patients with metastatic cancer, the total average ESAS score differed significantly according to the Eastern Cooperative Oncology Group (ECOG) performance scale from 34 in patients with an ECOG score of 1 to 70 in patients with an ECOG score…”
Section: Discussionsupporting
confidence: 71%
“…In lung cancer patients, moderate/severe fatigue is associated with significantly poorer PS 30 . This was confirmed in another study where there was a strong negative relationship between Karnofsky PS and the top four symptoms (pain, fatigue, disturbed sleep and distress) in lung cancer patients 31 .…”
Section: Esas Itemsupporting
confidence: 65%
“…A relationship has been identified in prior studies between symptom burden and performance status. 4,5 The prequalification to tolerate 3 hours of therapy per day may have reduced the numbers of patients with high symptom burdens from the study.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Lin et al found a strong relationship with pain, fatigue, disturbed sleep, distress and the Karnofsky Performance Scale in cancer patients. 4 Hung et al found a relationship between function and fatigue in non-small cell lung cancer survivors using the Karnofsky Self Report Performance Scale and the Brief Fatigue Inventory. 5 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 In one study, concurrent physical symptoms and psychosocial distress occurred in patients attending a cancer pain clinic compared to those who did not attend the pain clinic..…”
mentioning
confidence: 99%